Attitude scale towards LGBTI individuals: Validity and reliability study - Kübra Çiçek; Ayşe Turanlı; Ahmet Sapanci (Journal of Pedagogical Research, 2017)
The purpose of this study was to develop an instrument to measure university students' attitudes towards LGBTI individuals. The sample included 220 university students attended a public university located in the west of Turkey during 2016-2017 education year. The participants were 94 men and 126 women and their age ranged from 18 to 25. During the scale development process, a few steps have been followed. At first, items that had negative correlations with the scale have been removed from the analysis. Then exploratory factor analysis (EFA) has been performed. The results of EFA revealed 28 items loading three factors. These three factors explained 43.9% of the variance. For the reliability of the scale, the Cronbach's alpha reliability coefficient of the scale and its sub-dimensions have been found to be .95, .94, .81, and .70 respectively. The results of this study showed that the attitude scale towards LGBTI individuals is a valid and reliable scale.